KESADARAN JIWA DALAM MENCAPAI KEBAHAGIAAN MELALUI PENDIDIKAN YOGA MENURUT TUNTUNAN KATHA UPANISAD - Ida Ayu Nindia Brahmani Putri (Guna Widya: Jurnal Pendidikan Hindu, 2020)
In this life, humans are always overwhelmed by Tri Guna, this is what causes the turmoil of the human mind so that humans cannot look inside and only look outward. The result of this situation is to darken humanity from the nature of the atman and Brahman in him. Humans can not be separated from the pleasure that always lead to misery. Katha Upanisad states, wise people will choose happiness over pleasure, whereas fools think only about pleasure. To realize this self is only a container that is not eternal and belongs to Brahman, one of the paths that can be followed is through Yoga which has been arranged so neatly by Maha Rsi Patanjali. When Samadhi can be achieved there is a virtual existence can be realized so that the highest awareness of the existence of Brahman who animates every human being is able to eliminate the turmoil of rajas and tamas which always covers the soul. This awareness should always be trained through the path of yoga education that is routinely carried out.